Physical activity level among undergraduate students in Terengganu, Malaysia using pedometer - Noor Aini, Mohd Yusoff; Aryati, Ahmad; Mohd Razif, Shahril (2018)
A cross-sectional study determine physical activity level among 95 undergraduate students at UniSZA using pedometer. Subjects consented and completed socio-demographic details, weight and height were measured. Each subject was supplied with a pedometer and wear it for a week and record steps per day from the pedometer each night before bed. Descriptive statistic and independent T-test coefficient analyze the data using IBM SPSS version 22.0. Results showed that 66.4% of the subjects were classified as sedentary according to pedometer determined physical activity. Males recorded significantly more steps than female per day. Subjects in the age group of 18-20 years old had the highest mean average steps count than the older age group of 21-24 years old and ≥ 25 years old per day. Only 5.2% were classified as active and highly active using pedometer determined physical activity level.